الشيخ عبد الله بن فودي النيجيريّ وموقفه من التصوّف - Alawiye Abdul Mumin Abdur Razzaq; Abdul Manan Ismail; Shittu Bilal Yusuf; Ahmad Wifaq Mokhtar; Mushaddad Hasbullah (Universiti Sains Islam Malaysia, 2024)
This paper is to clarify the stand of Ibn F?di on Sufism. He emerged as one of the scholars during the nineteenth century, as a result of a great portion of knowledge given to him by Allah. The researchers used inductive, deductive and analytical methods. Meanwhile, this paper comprises three sections after the introduction. The first section treats the biography of Ibn Fudi. The second deals with his opinions on Sufism, while the third analyses his opinions and the general perspectives on Sufism. Finally, it is realised that Ibn Fudi was a scholar who used to follow the Islamic guidelines in his activities and frowned against all unconventional acts of the Sufi order.